A new method for determining PFASs by UHPLC-HRMS (Q-Orbitrap): Application to PFAS analysis of organic and conventional eggs sold in Italy. (1st February 2023) - Chiumiento, Francesco; Bellocci, Mirella; Ceci, Roberta; D'Antonio, Silvia; De Benedictis, Alfonso; Leva, Manuela; Pirito, Luigi; Rosato, Roberta; Scarpone, Rossana; Scortichini, Giampiero; Tammaro, Giulio; Diletti, Gianfranco
Highlights: A new sensitive method for the determination of 18 PFASs in eggs. PFAS levels in eggs were always close to the detection limits. No significant difference emerged among organic, barn and cage eggs. Children are the most exposed to PFASs. Abstract: Per- and polyfluoroalkyl substances (PFASs) are ubiquitous environmental pollutants with the ability to uptake to food and feed. Among food, fish, fruits and eggs are considered as major contributors to human dietary exposure. A new method was developed and validated for the simultaneous determination of 18 PFASs in eggs using isotope dilution followed by ultrahigh performance liquid chromatography coupled to high resolution mass spectrometry. The analysis of 132 samples (organic, barn and caged eggs) was performed. Levels were always close to the detection limits and no significant difference emerged among the 3 groups. The highest PFAS concentration in eggs was used to estimate the dietary exposure of different Italian population groups. As expected, children were more highly exposed than adults due to lower body weight. This data suggests that the recent tolerable weekly intake of 4.4 ng kg -1 b.w. could be exceeded when the cumulative intake arising from other food products is considered.